Evidence for Production of a New Lantibiotic (Butyrivibriocin OR79A) by the Ruminal Anaerobe Butyrivibrio fibrisolvens OR79: Characterization of the Structural Gene Encoding Butyrivibriocin OR79A - Kalmokoff, M. L. (American Society for Microbiology, 1999)
The ruminal anaerobe Butyrivibrio fibrisolvens OR79 produces a bacteriocin-like activity demonstrating a very broad spectrum of activity. An inhibitor was isolated from spent culture fluid by a combination of ammonium sulfate and acidic precipitations, reverse-phase chromatography, and high-resolution gel filtration. N-terminal analysis of the isolated inhibitor yielded a 15-amino-acid sequence (G-N/Q-G/P-V-I-L-X-I-X-H-E-X-S-M-N). Two different amino acid residues were detected in the second and third positions from the N terminus, indicating the presence of two distinct peptides. A gene with significant homology to one combination of the determined N-terminal sequence was cloned, and expression of the gene was confirmed by Northern blotting. The gene (bvi79A) encoded a prepeptide of 47 amino acids and a mature peptide, butyrivibriocin OR79A, of 25 amino acids. Significant sequence homology was found between this peptide and previously reported lantibiotics containing the double-glycine leader peptidase processing site. Immediately downstream of bvi79A was a second, partial open reading frame encoding a peptide with significant homology to proteins which are believed to be involved in the synthesis of lanthionine residues. These findings indicate that the isolated inhibitory peptides represent new lantibiotics. Results from both total and N-terminal amino acid sequencing indicated that the second peptide was identical to butyrivibriocin OR79A except for amino acid substitutions in positions 2 and 3 of the mature lantibiotic. Only a single coding region was detected when restriction enzyme digests of total DNA were probed either with an oligonucleotide based on the 5′ region of bvi79A or with degenerate oligonucleotides based on the predicted sequence of the second peptide.